Diagnostic value of pleural fluid T-SPOT for tuberculous pleurisy: An updated meta-analysis. (May 2020) - Luo, Ying; Xue, Ying; Guo, Xueyun; Lin, Qun; Tang, Guoxing; Yu, Jing; Mao, Liyan; Wang, Feng; Sun, Ziyong
Abstract: Background: Diagnosing tuberculous pleurisy (TP) remains a clinical challenge and the best method to diagnose it is controversial. Although several studies have investigated the performance of pleural fluid (PF) T-SPOT for pleural tuberculosis (plTB) diagnosis, the heterogeneity of its accuracy exists. Therefore, we performed an updated meta-analysis of the existing evidence on the utility of PF T-SPOT to diagnose TP. Methods: PubMed and EmBase were searched for relevant English articles up to July 29, 2019. Statistical analysis was performed using Stata, Revman, and Meta-Disc. Pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were determined. Summary receiver operating characteristic (SROC) curves and the area under the curve (AUC) were used to summarize the overall diagnostic performance. Results: A total of 13 studies (997 patients with TP and 656 patients without TP) were identified and enrolled to meta-analysis, giving the following pooled values for diagnostic accuracy of PF T-SPOT: sensitivity, 0.91 (95% CI, 0.89–0.92, I 2 = 80.9%); specificity, 0.88 (95% CI, 0.86–0.91, I 2 = 87.3%); PLR, 6.28 (95% CI, 2.88–13.69, I 2 = 93.3%); NLR, 0.12 (95% CI, 0.07–0.21, I 2 = 84.9%); DOR, 59.74 (95% CI, 24.13–147.93, I 2 = 78.3%); and the area under the SROC curve, 0.95 (95% CI, 0.93–0.97). Conclusions: Our meta-analysis suggests that PF T-SPOT has important diagnostic value for plTB. However, the standardization of the operating procedure needs to be further promoted, which would make the results more credible.